Legitimasi Hukum Asing Sebagai Pertimbangan Putusan oleh Mahkamah Konstitusi: Perbandingan Antara Indonesia dan Afrika Selatan - Zuhdi, Achmad; Kamula, Ari Ade (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2024)
The issue of referring to foreign law in constitutional deliberations often triggers criticism as "cherry picking". This research examines how the Constitutional Courts of Indonesia and South Africa use foreign law in their jurisprudence, focusing on its legitimacy and impact on the protection of human rights and democratic principles. The research uses a normative juridical method with comparative, statutory, and historical approaches by analysing decisions from both courts as well as relevant secondary sources. The findings show that both courts utilise foreign law but differ significantly in their approach. The South African Constitutional Court often cites foreign precedents directly, while the Indonesian Constitutional Court more often uses international law as a reference. The research concludes that the Constitutional Court's use of foreign law can enhance human rights and democracy jurisprudence if properly integrated into the national legal framework.